Alternatif Penyelesaian Masalah Peraturan Perundangan: Sebuah Pelajaran Penataan Kelembagaan (A Solution Alternative on Law and Regulations Problem: A Lesson of Institutional Arrangement) - Azis Khan (Institut Pertanian Bogor (IPB University), 2008)
This article is a conceptual review on Rova et. al. (2001) “When Regulation Fails: Vendace Fishery in the Gulf of Bothnia”. A relevant core message and its implication was drawn considered as a useful lesson learnt, especially for our future option on direction of natural resources management (NRM) reform, including that on forestry. There is a strong relationship between characteristic of natural resources, social conditions of its stakeholders and the institutional structure of its management. The institutional arrangement need to seriously taking into account this essential relationship; including efforts to guarantee that all resiliencies (institutional, managerial, social and ecological) are materialized. These resiliencies could be existed and mutually powerful if and only if the authority of the NRM was not centralized and was based on the NR characteristics by themselves. Need a serious institutional arrangement that is not just for having a restructured institution, but also have to materialize all the resiliencies and provide the consequences of having options for collective actions toward joint outcomes: the sustainability of the NRM. This is a core message actually implying to where the future NRM reform to be directed, especially from institution point of view.